Estimation of stature from percutaneous length of tibia in the population of Birgunj, Nepal - Sah, Rajendra Prasad; Shrestha, Iju (Journal of Kathmandu Medical College, 2014)
Background: Stature estimation is one of the important parameters in establishment of the identity of a person. As said “Identification is an individual’s birth right”, stature of an individual is an inherent character. Mass disasters like aircrash, terrorist attacks etc. are quite frequent these days because of which dismembered body parts are being frequently brought to the medico-legal experts for generating data for identification. Objective: The objective of this study is to estimate the stature from percutaneous tibia length (PCTL). Methods: This prospective study consisted of 150 males and 150 females between the age group of 20 to 30 years, born and brought up in Nepal. The duration of study is one year from October 2012 to October 2013. The parameters measured were stature and percutaneous tibia length. To find out the correlation of percutaneous tibial length with that of the height and to evolve a regression equation formula necessary statistical evaluation has been done on the data obtained from 300 adult participants comprising of 150 males and 150 females. By using the regression equation formula so derived the height of an individual can be calculated by the help of percutaneous tibial length. The data were analysed using Statistical Package for Social Sciences (SPSS) version 11. P value less than 0.05 was considered as a significant. Results: It was found that a significant positive correlation existed between the stature and percutaneous tibial length with a correlation coefficient (r) of 0.562 in males and 0.71 in females and p value <0.001. Stature was estimated from PCTL using simple regression analysis Stature (cm) = 88.898+2.027 * PCTL (cm) for males and Stature (cm) = 75.954+2.253 * PCTL (cm) for females. Conclusion: A highly significant correlation of stature was observed with percutaneous length in both sexes. The result of this study would be useful for anthropologists and forensic medicine experts. Stature can be estimated from PCTL using simple regression analysis. DOI: http://dx.doi.org/10.3126/jkmc.v3i2.11227 Journal of Kathmandu Medical College Vol. 3, No. 2, Issue 8, Apr.-Jun., 2014 Page : 58-62